An efficient and energy stable scheme for a phase‐field model for the moving contact line problem. (16th December 2015) - Aland, Sebastian; Chen, Feng
Summary: In this paper, we propose for the first time a linearly coupled, energy stable scheme for the Navier–Stokes–Cahn–Hilliard system with generalized Navier boundary condition. We rigorously prove the unconditional energy stability for the proposed time discretization as well as for a fully discrete finite element scheme. Using numerical tests, we verify the accuracy, confirm the decreasing property of the discrete energy, and demonstrate the effectiveness of our method through numerical simulations in both 2‐D and 3‐D. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In the study of the phase‐field model for the moving contact line problem, a linear and energy stable numerical scheme was proposed in the paper for solving the Navier‐Stokes‐Cahn‐Hilliard system subject to a new set of complex boundary conditions. Performance and visualization were provided in the work.